Experimental Investigation of Rubber Swelling in Bitumen. Issue 2 (February 2020) - Wang, Haopeng; Liu, Xueyan; Apostolidis, Panos; Erkens, Sandra; Skarpas, Athanasios
Rubber swelling in bitumen, which is a diffusion-induced volume expansion process, plays a dominant role in the design of crumb rubber modified bitumen binders and their properties development. This study aims to investigate the kinetics of bitumen diffusion into truck tire rubber, the equilibrium swelling characteristics of rubber, and the mechanical properties of rubber before and after swelling at different high temperatures. Fourier transform infrared spectroscopy results indicate that no rubber dissolution happens during the interaction in the temperature range from 160°C to 200°C. Aliphatic compounds from bitumen preferentially diffused into rubber during the swelling process. The diffusion coefficients of bitumen into rubber were determined by the sorption test using the gravimetric method. The diffusion coefficient increases with the increase of temperature in an Arrhenius form. The volume expansion of rubber during swelling was captured by the X-ray computed tomography scan images. Rubber swells faster at the earlier stages, then the expansion rate slows down. The swelling ratio of rubber increased from 1.97 at 160°C to 3.03 at 200°C after 36 h interaction. Mechanical tests by dynamic shear rheometer reveal that swollen rubber becomes softer compared with the dry rubber and exhibits obvious viscoelastic behaviors. With the increase of temperature, the softening and viscous effect are more significant. The obtained parameters can be implemented to swelling and micromechanical models to better predict the binder properties.